Vers un nouvel équilibre monétaire international : un colloque du 46e congrès de l’ACFAS - Cameron, Duncan; Saint-Germain, Maurice (L'Actualité économique)

(untitled) (HEC Montréal, 1979)
International monetary questions were chosen by the economics section of ACFAS as the theme of a round table held at the University of Ottawa in May 1978. This article summarizes the discussions amongst Professors V. Leroy and B. Decaluwé, and the Deputy Governor of the Bank of Canada, Alain Jubinville. Each participant outlined his views on the principal issues: flexible echange rates, intervention policies, and resevre requirements. A question and answer period followed the presentations and the topics raised included the role of multinational enterprises, the plight of the Third World, the significance of the accumulation of petro-dollars, and the effects of a weaker dollar on the international payments system. The article then compares the approaches taken by Professors Decaluwé, Leroy and Cameron in the articles regrouped in this issue of L'Actualité Economique as well as that taken by Professor Nappi in his article in the April-June 1978 issue. In conclusion the questions raised at the colloquium are updated by reference to three new elements which have appeared in the last year: the economic summit in Bonn, the European Monetary System, and the agreed second allocation of Special Drawing Rights.